Pemberian Bubur Tempe Instan dan Sediaan Komersial Diabetes pada Pasien Diabetes Melitus Tipe 2, Kanker Kaput Pankreas, dan Hipoalbuminemia: Studi Kasus: Laporan Kasus - Devi, Ni Putu Destriani; Herawati, Ni Putu Elsa (PT Kalbe Farma Tbk., 2026)
Introduction: Patients with diabetes mellitus and caput pancreas cancer generally experience decreased food intake due to gastrointestinal complaints, such as abdominal pain, nausea, vomiting, and feeling full. This condition can be managed by providing small portions of nutrientdense and easily digested food to prevent decline in nutritional status and patient condition. Case: A 58-year-old male with right upper abdominal pain, fever, and white stools was treated for caput pancreas cancer and hypoalbuminemia. History of type 2 diabetes mellitus for 2years and biliary stent placement. Food intake at home is < 25% of the requirement. The patient is underweight with body mass index (BMI) 16 kg/m2, hypoalbuminemia (2.6 g/dL), and hyperglycemia (random glucose 220 mg/dL). This nutritional intervention aims to gradually optimizefood intake (target > 80% requirement) in 5 days, with easily digestible and low glycemic index food in the form of modification of instant tempeh porridge and commercial diabetic preparation in small portion. Discussion: The nutritional intervention is acceptable to the patient.Conclusion: Modified instant tempeh porridge and commercial diabetic preparation can increase patient intake with good acceptance and improve gastrointestinal tolerance.